2009
DOI: 10.1590/s0103-05822009000100010
|View full text |Cite
|
Sign up to set email alerts
|

Consistência das informações de um estudo sobre o impacto da assistência nutricional no atendimento pré-natal

Abstract: OBJETIVO: Avaliar a consistência dos dados obtidos no estudo Avaliação do impacto da assistência nutricional pré-natal no resultado obstétrico, por análise da confiabilidade das informações e perdas de seguimento ocorridas. MÉTODOS: Trata-se de um estudo de intervenção, prospectivo, em uma coorte de gestantes. O grupo pré-intervenção (GI) foi constituído de 225 puérperas adultas (1999-2001) e o grupo intervenção (GII), de 208 gestantes adultas (2005-2006) e seus respectivos recém-nascidos, atendidos em Materni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Nevertheless, a national study in a similar population showed good reliability (ICC = 0.96; 95% CI, 0.94-0.98) between prepregnancy weight reported by the mother, covering the period up to 2 months before conception, and weight measured until the 13th week of gestation. 49 Saunders et al 49 recommended that self-reported prepregnancy weight should be preferentially used to estimate BMI, because although the GWG in the first quarter is lower as compared to other periods of pregnancy, this can occur with a range of 0.9 kg to 2.3 kg.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a national study in a similar population showed good reliability (ICC = 0.96; 95% CI, 0.94-0.98) between prepregnancy weight reported by the mother, covering the period up to 2 months before conception, and weight measured until the 13th week of gestation. 49 Saunders et al 49 recommended that self-reported prepregnancy weight should be preferentially used to estimate BMI, because although the GWG in the first quarter is lower as compared to other periods of pregnancy, this can occur with a range of 0.9 kg to 2.3 kg.…”
Section: Discussionmentioning
confidence: 99%
“…A realização de treinamento, a supervisão das equipes, a cogestão, o monitoramento dos dados e a compreensão do processamento das informações têm sido indispensáveis para o aperfeiçoamento dos sistemas de vigilância [15][16][17] .…”
Section: Discussionunclassified
“…Women diagnosed as having hypertension were also investigated for the presence of proteinuria, with >300 mg protein in urine in 24 h being interpreted as indicative of preeclampsia, and this value in association with seizures as being eclampsia. Other complications, like urinary infection and premature rupture of membranes, were identified by consulting the medical records [18,19]. …”
Section: Methods and Study Designmentioning
confidence: 99%